Analisis Yuridis Penggunaan Dokumen di Bawah Tangan dalam Transaksi Tanah Nominee dan Implikasinya terhadap Penyelesaian Sengketa Perdata: Studi Putusan Kasasi Nomor 753 K/Pdt/2023 - Ayu Sartika Simatupang (Jurnal Hukum Lex Generalis, 2026)
Land control disputes involving nominee arrangements have increasingly emerged in Indonesian judicial practice, despite Article 21 paragraph (1) of Law Number 5 of 1960 concerning Basic Agrarian Principles prohibiting foreign nationals from holding ownership rights over land. This issue is reflected in Supreme Court Decision Number 753 K/Pdt/2023, which arose from a land control dispute in Badung Regency, Bali. This study employs normative legal research. The findings indicate that private documents used in nominee relationships do not receive legal recognition because they contravene Article 21 of the Basic Agrarian Law and are therefore null and void by operation of law. Nominee relationships demonstrate a separation between the legal owner and the beneficial owner, resembling a trustee arrangement; however, such relationships lack legitimacy within Indonesia’s land law system. Supreme Court Decision Number 753 K/Pdt/2023 affirms that nominee arrangements constitute a form of circumvention of the law.